Teacher and Student’s Self-Directed Learning Readiness in Using Technology in the Urgency of Online Learning - Oktariani, Ni Luh Tu; Santosa, Made Hery; Pratiwi, Ni Putu Astiti (The Art of Teaching English as a Foreign Language (TATEFL), 2022)
Education nowadays shifted from face-to-face learning into online learning. Teacher and student readiness are the essential factors to the success of online learning. The present study aims to analyze the teacher and student’s self-directed learning readiness in using the technology in the urgency of remote education. The participants were an English teacher and a student of SMP Negeri 2 Melaya. The data collection was done by interviewing and observing the teacher and student in online learning. The instruments were an interview guide and an observation checklist. The data analysis was implemented the interactive model analysis. It involved data collection, data reduction, data display, and conclusion. The results showed that the teacher and student were ready to use the technology in online learning analyzed by their self-directed learning. The result of perceived and observed readiness showed similar results. The results of the current research is the same as the previous reserch which most of the students observed that they have good self-directed learning in learning. It also supported by the participants which familiar on using the technology.